Study of Adding Ethanol to Gasoline Effects on Produced Noise Intensity of Single Cylinder Spark Ignition Engine - Saleh, Adel Mahmoud (Al-Khwarizmi Engineering Journal, 2011)
Since 1990 internal combustion engines and variable systems has been considered as emission. Noise can be defined as undesirable sound, and in high levels it can be considered ahealth hazard. Large internal combustion engines produce high levels of noise. In many countries there are laws restricting the noise levels in large engine rooms and fixed applications. Locomotives engines have the minimum emission influence because of noise control techniques capability. In this paper study on a single cylinder internal combustion engine was conducted. The engine works by adding ethanol to gasoline, at variable speeds, without adding ethanol, and with adding 10 and 20% ethanol in volumetric ratio. Using one sound insulator or two or without using sound insulator. The results show that noise increased with engine speed increase. Adding ethanol didn’t affect noise produced by engine. The study demonstrates that using one insulator is enough to reduce noise with high percentage.